MLCC release film base film and preparation method thereof
Through the combination of special polyester slices and modified masterbatch and the introduction of nucleating agents, an MLCC release film with three-layer coextruded structure was designed, which solved the difficulty in meeting high stiffness and high flatness at the same time in the prior art. The problem of degree has achieved mechanical and thermal stress stability in the MLCC manufacturing process, and meets the requirements of the release film base film for thin-layer MLCC.
Patent Information
- Application Number
- CN202411586658.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The MLCC release film base film in the prior art is difficult to meet the requirements of high stiffness and high flatness at the same time, resulting in mechanical stress and thermal stress stability problems in the MLCC manufacturing process.
Using the combination of special polyester slices and modified masterbatch, the mechanical properties and dimensional stability of the film are enhanced through the design of ABC three-layer coextrusion structure, and nucleating agents are introduced in the synthesis process of special polyester slices to improve poly Crystallization and high temperature stability of the ester.
The excellent stiffness, flatness and dimensional stability of the MLCC release film are achieved, while the roughness is reduced, meeting the requirements of the release film base film for MLCC thin-layering, and maintaining mechanical properties under high temperature environments.
Smart Images

Figure DIWG7AGEJZCI7NCBARBKBUOQURBEC0DQ8DQZNBD2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polyester films, and in particular to an MLCC release film base film and a preparation method thereof. Background Art
[0002] MLCC, short for chip multilayer ceramic capacitor, is a basic passive electronic component. With the rapid development of 5G communications and new energy vehicles, the use of MLCC has increased dramatically. The manufacturing process of MLCC is to evenly apply the ceramic slurry on the release film, print the electrode on the surface of the ceramic layer after drying, and then remove the release film. The ceramic layer is completed through stacking, capping, lamination, debinding, sintering, chamfering, termination, burning end, terminal processing, appearance selection, testing, packaging and other processes. As a high-consumption auxiliary material in the MLCC manufacturing process, the MLCC release film changes in conjunction with the production quantity of MLCC, and the market is showing a clear expansion trend.
[0003] As MLCC develops towards thinner and more multi-layered, the performance requirements for the release film base film are also increasing. The ideal MLCC release film base film should have high flatness and low roughness to ensure that the MLCC release film has uniform release force, which is crucial to ensure the stacking quality of the ceramic medium and the electrical properties of the MLCC; at the same time, in order to withstand the mechanical and thermal stresses in the production process, the MLCC release film base film also needs to have high stiffness to maintain its stability in the coating, drying, printing electrode and other processes.
[0004] However, the MLCC release film base film in the prior art often finds it difficult to meet the above requirements at the same time. On the one hand, in order to improve the flatness of the film, fine raw materials and complex surface treatment processes are usually required, which not only increases the production cost, but also sacrifices the stiffness of the material; on the other hand, in order to improve the stiffness, increasing the thickness of the material or using higher strength raw materials will lead to a decrease in flatness.
[0005] Therefore, how to prepare a polyester film with excellent stiffness and flatness is a key technical difficulty. Summary of the invention
[0006] In order to solve the problem that the polyester film in the prior art cannot have both excellent flatness and excellent stiffness, the present invention discloses an MLCC release film base film, which introduces special polyester chips and modified masterbatch prepared by a specific method, so that the prepared MLCC release film base film has excellent stiffness, flatness and dimensional stability; in addition, the present invention introduces a nucleating agent during the synthesis process of the special polyester chips, which not only enhances the mechanical properties of the film, but also ensures its stability in a high temperature environment, thereby meeting the requirements of high-end MLCC release films.
[0007] The technical solution adopted by the present invention to solve its technical problem is: An MLCC release film base film, wherein the MLCC release film base film is an ABC three-layer co-extrusion structure, wherein layers A and C are surface layers, and layer B is a core layer; The materials of the A layer include the following components in parts by weight: Special polyester chips 70-95 pieces; Modified masterbatch 5-30 parts; The materials of the B layer include the following components in parts by weight: Special polyester chips 90-98 pieces; 2-10 portions of high-speed material; The materials of the C layer include the following components in parts by weight: 50-80 pieces of special polyester chips; Special masterbatch 20-50 parts; The special polyester chips are prepared by esterifying and polycondensing a mixture of polyethylene terephthalate and polyethylene naphthalate with polyol, and then adding a nucleating agent and extruding and granulating.
[0008] Optionally, the special polyester chips are prepared according to the following method: (1) Mix terephthalic acid and 2,6-naphthalene dicarboxylic acid in a container to obtain a mixture, then add ethylene glycol, a catalyst, and a stabilizer, and react at 90-120°C for 2-4 hours under the protection of an inert gas, then raise the temperature to 190-250°C, and continue to react for 4-6 hours to complete the esterification reaction; (2) The pressure is reduced to 10-60 Pa, and the temperature is increased to 240-265°C. The polycondensation reaction is continued for 5-12 hours. The obtained polycondensate is mixed with a nucleating agent, and granulated by melt extrusion to obtain special polyester chips.
[0009] Optionally, the mass ratio of terephthalic acid to 2,6-naphthalene dicarboxylic acid is (1.5~9):1.
[0010] Optionally, the molar mass ratio of the mixture to ethylene glycol is 1:(1-1.1).
[0011] Optionally, the added amount of the catalyst is (0.1-0.3)% of the total mass of the mixture; the added amount of the stabilizer is (0.02-0.2)% of the total mass of the mixture.
[0012] Optionally, the nucleating agent is ethylene acrylic acid ionomer.
[0013] Optionally, the modified masterbatch is prepared according to the following method: the antiblocking agent filler is blended with special polyester chips and a dispersant, and the mixture is granulated by twin-screw extrusion.
[0014] Optionally, the particle size of the opening agent filler is 0.3-2.2 μm.
[0015] Optionally, the addition amount of the opening agent filler is (0.6-3)% of the mass of the special polyester chips.
[0016] Another object of the present invention is to provide a method for preparing the MLCC release film base film as described above, characterized in that it comprises the following steps: S1: According to the formula, the A layer, the B layer and the C layer are sent to the extruder for melt extrusion; S2: After passing through the die, the melt is cast behind the chilled roller to form a thick sheet. After longitudinal stretching, transverse stretching, shaping, cooling, pulling and winding, the MLCC release film base film is obtained.
[0017] The present invention has the following beneficial effects: The MLCC release film base film provided by the present invention adopts special polyester chips as the polyester film base material, and through combination with a modified masterbatch, as well as the synergistic effect of the various components, the prepared MLCC release film base film has excellent stiffness, flatness and dimensional stability, and also has lower roughness, meeting the requirements of MLCC thin-layer release film base film; in addition, the present invention introduces a nucleating agent during the synthesis process of the special polyester chips, which not only promotes the crystallization of polyester, but also effectively prevents the degradation of polyester at high temperatures, thereby ensuring the excellent mechanical properties of the polyester film while also ensuring its stability in a high temperature environment. DETAILED DESCRIPTION
[0018] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0019] In order to solve the problem that the polyester film in the prior art cannot have excellent flatness and excellent stiffness, the present invention provides an MLCC release film base film, and the MLCC release film base film is an ABC three-layer co-extrusion structure, wherein the A and C layers are surface layers, and the B layer is a core layer; The materials of layer A include the following components in parts by weight: Special polyester chips 70-95 parts; Modified masterbatch 5-30 parts; The materials of layer B include the following components in parts by weight: Special polyester chips 90-98 pieces; 2-10 portions of high-speed material; The materials of layer C include the following components in parts by weight: 50-80 pieces of special polyester chips; Special masterbatch 20-50 parts; Special polyester chips are made by esterifying and polycondensing a mixture of polyethylene terephthalate and polyethylene naphthalate with polyols, and then adding a nucleating agent and extruding and granulating.
[0020] The MLCC release film base film provided by the present invention adopts special polyester chips as the polyester film base material, and through combination with a modified masterbatch, as well as the synergistic effect of the various components, the prepared MLCC release film base film has excellent stiffness, flatness and dimensional stability, and also has lower roughness, meeting the requirements of MLCC thin-layer release film base film; in addition, the present invention introduces a nucleating agent during the synthesis process of the special polyester chips, which not only promotes the crystallization of polyester, but also effectively prevents the degradation of polyester at high temperatures, thereby ensuring the excellent mechanical properties of the polyester film while also ensuring its stability in a high temperature environment.
[0021] Specifically, in order to further improve the processing stability of the film during high-speed production, the present invention preferably selects at least one of the high-speed materials from Yizheng Chemical Fiber FG6200 and Takemoto Oil S-626.
[0022] In order to improve the optical properties and opening of the film, the present invention preferably uses a special masterbatch selected from at least one of Yizheng Chemical Fiber FG611, Yizheng Chemical Fiber FG616, Takemoto Oil X-006, and Fosu 171-2.
[0023] The present invention preferably prepares the above-mentioned special polyester chips according to the following method: (1) Mix terephthalic acid and 2,6-naphthalene dicarboxylic acid in a container to obtain a mixture, then add ethylene glycol, a catalyst, and a stabilizer, and react at 90-120°C for 2-4 hours under the protection of an inert gas, then raise the temperature to 190-250°C, and continue to react for 4-6 hours to complete the esterification reaction; (2) The pressure is reduced to 10-60 Pa, and the temperature is increased to 240-265°C. The polycondensation reaction is continued for 5-12 hours. The obtained polycondensate is mixed with a nucleating agent, and granulated by melt extrusion to obtain special polyester chips.
[0024] During the synthesis process of the special polyester chips, 2,6-naphthalene dicarboxylic acid, which has a structure similar to terephthalic acid, is added. The obtained special polyester chips have greater rigidity. At the same time, the addition of ionomer nucleating agent can promote the crystallization of polyester and avoid the degradation of polyester under high temperature conditions, thereby ensuring the mechanical properties of polyester, so that the polyester film prepared by the special polyester chips has better stiffness, flatness and dimensional stability.
[0025] In order to further improve the comprehensive performance of the product, the present invention preferably has a mass ratio of terephthalic acid to 2,6-naphthalene dicarboxylic acid of (1.5-9):1, wherein 2,6-naphthalene dicarboxylic acid accounts for 10-40% of the total mass of the mixture of the two.
[0026] The preferred molar mass ratio of the mixture to ethylene glycol in the present invention is 1: (1-1.1), thereby ensuring the balance and completeness of the reaction of the polyester chips during the synthesis process.
[0027] The preferred catalyst of the present invention is prepared by mixing antimony ethylene glycol, butyl titanate and p-toluenesulfonic acid in a mass ratio of 1:1:(1.5-1.8); and the preferred amount of the catalyst added is (0.1-0.3)% of the total mass of the mixture.
[0028] The preferred stabilizer of the present invention is triphenyl phosphite; and the preferred amount of the stabilizer added is (0.02-0.2)% of the total mass of the mixture.
[0029] The preferred nucleating agent of the present invention is ethylene acrylic acid ionomer; further, the preferred nucleating agent of the present invention is at least one selected from Surlyn resin of DuPont and AClyn of Honeywell.
[0030] Since excessive nucleating agent will be wasteful and unstable, and insufficient nucleating agent will have little effect, the addition of nucleating agent in an appropriate proportion can greatly increase the density of crystal nuclei, resulting in a significant reduction in the size of spherulites, thereby effectively improving the optical properties of the film; further, the preferred amount of nucleating agent added in the present invention is (0.5-1.8)% of the mass of the polycondensate.
[0031] The preferred modified masterbatch of the present invention is prepared according to the following method: the antiblocking agent filler is blended with the special polyester chips and the dispersant, and the mixture is extruded and granulated by a twin-screw.
[0032] The preferred opening agent filler of the present invention is selected from at least one of silicon dioxide, calcium carbonate, montmorillonite and barium sulfate.
[0033] The preferred particle size of the opening agent filler of the present invention is 0.3-2.2 μm.
[0034] The preferred addition amount of the anti-blocking agent filler in the present invention is (0.6-3)% of the mass of the special polyester chips.
[0035] The preferred dispersant of the present invention is polyethylene glycol-20000; and the preferred amount of the dispersant added is (0.8-4.2)% of the mass of the special polyester chips.
[0036] The modified masterbatch prepared by the present invention avoids the problems of uneven dispersion and aggregation of the open filler by adding an open filler with a small particle size and uniformly dispersing the dispersant in the system; thereby, the polyester film prepared by using the modified masterbatch has a lower roughness, meeting the requirements of the release film base film for MLCC thin-layer.
[0037] Another object of the present invention is to provide a method for preparing the MLCC release film base film as described above, comprising the following steps: S1: According to the formula, layer A, layer B and layer C are dried in a drying tower at 170-185°C for 3-5 hours, and then vacuumed and sent to the surface layer 1 extruder, the core layer extruder and the surface layer 2 extruder for melt extrusion; S2: After passing through the three-layer co-extrusion die, the melt is cast onto a casting roll at 18-40°C to form a casting; the casting is preheated to 78-90°C by a longitudinal preheating roll, instantly heated to 100-120°C by an infrared lamp, and then longitudinally stretched 2.8-4.3 times. After stretching, it is quickly cooled by a cooling roll at 25-35°C to form a unidirectional sheet; the unidirectional sheet is preheated at 100-120°C, stretched 3.8-4.7 times transversely at 125-135°C, and fixed at 235-245°C for 10-30 seconds and then cooled at 50-180°C. After traction and winding, the MLCC release film base film is obtained.
[0038] The method for preparing the MLCC release film base film provided by the present invention has a simple preparation process and is easy to operate, and realizes an efficient and stable production process through precisely controlled process steps; and by optimizing the raw material ratio and processing conditions, the production cost is effectively reduced while ensuring the processing performance of the product; in addition, the method has strong applicability, so that it can flexibly adapt to diverse production needs.
[0039] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0040] Unless otherwise specified, the high-speed materials in the embodiments of the present invention and the comparative examples are all Yizheng Chemical Fiber FG6200; the special masterbatch is Yizheng Chemical Fiber FG611; the stabilizer is triphenyl phosphite; the catalyst is a mixture of ethylene glycol antimony, butyl titanate, and p-toluenesulfonic acid in a mass ratio of 1:1:1.8; the nucleating agent is Surlyn resin from DuPont; the opening agent filler is silicon dioxide, and the particle size is 0.3-2.2 μm; the dispersant is polyethylene glycol-20000; the amount of materials used in each embodiment and the comparative example is measured in parts by weight.
[0041] An MLCC release film base film, which is an ABC three-layer co-extrusion structure, wherein the A and C layers are surface layers, and the B layer is a core layer; The materials of layer A include the following components in parts by weight: 70 pieces of special polyester chips; 30 parts of modified masterbatch; The materials of layer B include the following components in parts by weight: 90 pieces of special polyester chips; 10 portions of high-speed material; The materials of layer C include the following components in parts by weight: 50 pieces of special polyester chips; 50 parts of special masterbatch; The special polyester chips are prepared as follows: (1) Mix terephthalic acid and 2,6-naphthalene dicarboxylic acid in a container to obtain a mixture, then add ethylene glycol, a catalyst, and a stabilizer, and react at 90°C for 2 hours under the protection of an inert gas, then increase the temperature to 190°C and continue to react for 4 hours to complete the esterification reaction; (2) The pressure was reduced to 10 Pa, and the temperature was increased to 240°C. The polycondensation reaction was continued for 5 hours. The obtained polycondensate was mixed with a nucleating agent, and granulated by melt extrusion to obtain special polyester chips.
[0042] Specifically, the mass ratio of terephthalic acid to 2,6-naphthalene dicarboxylic acid is 1.5:1; the molar mass ratio of the mixture to ethylene glycol is 1:1; the amount of catalyst added is 0.1% of the total mass of the mixture; the amount of stabilizer added is 0.02% of the total mass of the mixture; and the amount of nucleating agent added is 0.5% of the mass of the polycondensate.
[0043] The modified masterbatch was prepared as follows: (1) Add the anti-blocking agent filler, dispersant and special polyester chips into a high-speed mixer for preliminary mixing. The speed of the high-speed mixer is set to 900 rpm and mixed for 20 minutes to obtain a preliminary mixture; (2) The preliminary mixed material is transferred to the feeding port of a twin-screw melt extruder, melt-extruded at 150°C, and granulated after cooling to obtain a modified masterbatch.
[0044] Specifically, the added amount of the antiblocking agent filler is 0.6% of the mass of the special polyester chips; and the added amount of the dispersant is 0.8% of the mass of the special polyester chips.
[0045] The method for preparing the MLCC release film base film comprises the following steps: S1: According to the formula, layer A, layer B and layer C are dried in a drying tower at 170°C for 3 hours, and then vacuumed and sent to the surface layer 1 extruder, the core layer extruder and the surface layer 2 extruder for melt extrusion; S2: After passing through the three-layer co-extrusion die, the melt is cast onto a casting roll at 18°C to form a casting; the casting is preheated to 78°C by a longitudinal preheating roll, instantly heated to 100°C by an infrared lamp, and then stretched 2.8 times longitudinally. After stretching, it is quickly cooled by a cooling roll at 25°C to form a unidirectional sheet; the unidirectional sheet is preheated at 100°C, stretched 3.8 times transversely at 125°C, and fixed at 235°C for 10 seconds and then cooled at 50°C. After traction and winding, the MLCC release film base film is obtained.
[0046] An MLCC release film base film, which is an ABC three-layer co-extrusion structure, wherein the A and C layers are surface layers, and the B layer is a core layer; The materials of layer A include the following components in parts by weight: 95 parts of special polyester chips; 5 parts of modified masterbatch; The materials of layer B include the following components in parts by weight: 98 pieces of special polyester chips; 2 portions of high-speed material; The materials of layer C include the following components in parts by weight: 80 pieces of special polyester chips; Special masterbatch 20 parts; The special polyester chips are prepared as follows: (1) Terephthalic acid and 2,6-naphthalene dicarboxylic acid are mixed in a container to obtain a mixture, and then ethylene glycol, a catalyst, and a stabilizer are added. Under the protection of an inert gas, the mixture is reacted at 120° C. for 4 hours, and the temperature is increased to 250° C. and the reaction is continued for 6 hours to complete the esterification reaction; (2) The pressure was reduced to 160 Pa, and the temperature was increased to 265°C. The polycondensation reaction was continued for 12 hours. The obtained polycondensate was mixed with a nucleating agent, and granulated by melt extrusion to obtain special polyester chips.
[0047] Specifically, the mass ratio of terephthalic acid to 2,6-naphthalene dicarboxylic acid is 9:1; the molar mass ratio of the mixture to ethylene glycol is 1:1.1; the amount of catalyst added is 0.3% of the total mass of the mixture; the amount of stabilizer added is 0.2% of the total mass of the mixture; and the amount of nucleating agent added is 1.8% of the mass of the polycondensate.
[0048] The modified masterbatch was prepared as follows: (1) Add the anti-blocking agent filler, dispersant and special polyester chips into a high-speed mixer for preliminary mixing. The speed of the high-speed mixer is set to 1000 rpm and mixed for 30 minutes to obtain a preliminary mixture; (2) The preliminary mixed material is transferred to the feeding port of a twin-screw melt extruder, melt-extruded at 270°C, and granulated after cooling to obtain a modified masterbatch.
[0049] Specifically, the amount of the opening agent filler added is 3% of the mass of the special polyester chips; the amount of the dispersant added is 4.2% of the mass of the special polyester chips.
[0050] The method for preparing the MLCC release film base film comprises the following steps: S1: According to the formula, layer A, layer B and layer C are dried in a drying tower at 185°C for 5 hours, and then vacuumed and sent to the surface layer 1 extruder, the core layer extruder and the surface layer 2 extruder for melt extrusion; S2: After passing through the three-layer co-extrusion die, the melt is cast onto a casting roll at 40°C to form a casting; the casting is preheated to 90°C by a longitudinal preheating roll, instantly heated to 120°C by an infrared lamp, and then longitudinally stretched 4.3 times. After stretching, it is quickly cooled by a cooling roll at 35°C to form a unidirectional sheet; the unidirectional sheet is preheated at 120°C, transversely stretched 4.7 times at 135°C, and fixed at 245°C for 30 seconds and then cooled at 180°C. After traction and winding, the MLCC release film base film is obtained.
[0051] An MLCC release film base film, which is an ABC three-layer co-extrusion structure, wherein the A and C layers are surface layers, and the B layer is a core layer; The materials of layer A include the following components in parts by weight: 80 pieces of special polyester chips; Modified masterbatch 20 parts; The materials of layer B include the following components in parts by weight: 95 parts of special polyester chips; 5 portions of high-speed material; The materials of layer C include the following components in parts by weight: 60 pieces of special polyester chips; 40 parts of special masterbatch; The special polyester chips are prepared as follows: (1) Terephthalic acid and 2,6-naphthalene dicarboxylic acid are mixed in a container to obtain a mixture, and then ethylene glycol, a catalyst, and a stabilizer are added. Under the protection of an inert gas, the mixture is reacted at 100° C. for 3 hours, and the temperature is raised to 230° C. and the reaction is continued for 5 hours to complete the esterification reaction; (2) The pressure was reduced to 30 Pa, and the temperature was increased to 250°C. The polycondensation reaction was continued for 8 hours. The obtained polycondensate was mixed with a nucleating agent, and granulated by melt extrusion to obtain special polyester chips.
[0052] Specifically, the mass ratio of terephthalic acid to 2,6-naphthalene dicarboxylic acid is 5:1; the molar mass ratio of the mixture to ethylene glycol is 1:1; the amount of catalyst added is 0.2% of the total mass of the mixture; the amount of stabilizer added is 0.1% of the total mass of the mixture; and the amount of nucleating agent added is 1% of the mass of the polycondensate.
[0053] The modified masterbatch was prepared as follows: (1) Add the anti-blocking agent filler, dispersant and special polyester chips into a high-speed mixer for preliminary mixing. The speed of the high-speed mixer is set to 950 rpm and mixed for 25 minutes to obtain a preliminary mixture; (2) The preliminary mixed material is transferred to the feeding port of a twin-screw melt extruder, melt-extruded at 200°C, and granulated after cooling to obtain a modified masterbatch.
[0054] Specifically, the amount of the opening agent filler added is 2% of the mass of the special polyester chips; the amount of the dispersant added is 3% of the mass of the special polyester chips.
[0055] The method for preparing the MLCC release film base film comprises the following steps: S1: According to the formula, layer A, layer B and layer C are dried in a drying tower at 180°C for 4 hours, and then vacuumed and sent to the surface layer 1 extruder, the core layer extruder and the surface layer 2 extruder for melt extrusion; S2: After passing through the three-layer co-extrusion die, the melt is cast onto a casting roll at 30°C to form a casting; the casting is preheated to 85°C by a longitudinal preheating roll, instantly heated to 110°C by an infrared lamp, and then stretched 3.5 times longitudinally. After stretching, it is quickly cooled by a cooling roll at 30°C to form a unidirectional sheet; the unidirectional sheet is preheated at 110°C, stretched 4.2 times transversely at 130°C, and fixed at 240°C for 20 seconds and then cooled at 100°C. After traction and winding, the MLCC release film base film is obtained.
[0056] An MLCC release film base film, which is an ABC three-layer co-extrusion structure, wherein the A and C layers are surface layers, and the B layer is a core layer; The materials of layer A include the following components in parts by weight: 85 pieces of special polyester chips; Modified masterbatch 15 parts; The materials of layer B include the following components in parts by weight: 96 pieces of special polyester chips; 4 portions of high-speed material; The materials of layer C include the following components in parts by weight: 70 pieces of special polyester chips; 30 parts of special masterbatch; The special polyester chips are prepared as follows: (1) Terephthalic acid and 2,6-naphthalene dicarboxylic acid are mixed in a container to obtain a mixture, and then ethylene glycol, a catalyst, and a stabilizer are added. Under the protection of an inert gas, the mixture is reacted at 110° C. for 2 hours, and the temperature is raised to 190° C. and the reaction is continued for 5 hours to complete the esterification reaction; (2) The pressure was reduced to 40 Pa and the temperature was increased to 240°C. The polycondensation reaction was continued for 10 hours. The obtained polycondensate was mixed with a nucleating agent and granulated by melt extrusion to obtain special polyester chips.
[0057] Specifically, the mass ratio of terephthalic acid to 2,6-naphthalene dicarboxylic acid is 8:1; the molar mass ratio of the mixture to ethylene glycol is 1:1; the amount of catalyst added is 0.3% of the total mass of the mixture; the amount of stabilizer added is 0.2% of the total mass of the mixture; and the amount of nucleating agent added is 1.5% of the mass of the polycondensate.
[0058] The modified masterbatch was prepared as follows: (1) Add the anti-blocking agent filler, dispersant and special polyester chips into a high-speed mixer for preliminary mixing. The speed of the high-speed mixer is set to 900 rpm and mixed for 30 minutes to obtain a preliminary mixture; (2) The preliminary mixed material is transferred to the feeding port of a twin-screw melt extruder, melt-extruded at 270°C, and granulated after cooling to obtain a modified masterbatch.
[0059] The modified masterbatch is prepared according to the following method: the antiblocking agent filler is blended with the special polyester chips and the dispersant, and the mixture is granulated by twin-screw extrusion.
[0060] Specifically, the added amount of the antiblocking agent filler is 1% of the mass of the special polyester chips; the added amount of the dispersant is 1% of the mass of the special polyester chips.
[0061] The method for preparing the MLCC release film base film comprises the following steps: S1: According to the formula, layer A, layer B and layer C are dried in a drying tower at 170-185°C for 3 hours, and then vacuumed and sent to the surface layer 1 extruder, the core layer extruder and the surface layer 2 extruder for melt extrusion; S2: After passing through the three-layer co-extrusion die, the melt is cast onto a casting roll at 18°C to form a casting; the casting is preheated to 90°C by a longitudinal preheating roll, instantly heated to 110°C by an infrared lamp, and then stretched 3 times longitudinally. After stretching, it is quickly cooled by a 30°C cooling roll to form a unidirectional sheet; the unidirectional sheet is preheated at 120°C, stretched 3.8 times transversely at 135°C, and fixed at 235°C for 30 seconds and then cooled at 50°C. After traction and winding, the MLCC release film base film is obtained.
[0062] Comparative Example 1 An MLCC release film base film, which is an ABC three-layer co-extrusion structure, wherein the A and C layers are surface layers, and the B layer is a core layer; The materials of layer A include the following components in parts by weight: 70 parts of FG600 base film-grade polyester chips; 2 parts of nucleating agent; 30 parts of modified masterbatch; The materials of layer B include the following components in parts by weight: 90 parts of FG600 base film-grade polyester chips; 10 portions of high-speed material; The materials of layer C include the following components in parts by weight: 50 parts of FG600 base film-grade polyester chips; 50 parts of special masterbatch; The modified masterbatch was prepared as follows: (1) Add the anti-blocking agent filler, dispersant and special polyester chips into a high-speed mixer for preliminary mixing. The speed of the high-speed mixer is set to 900 rpm and mixed for 20 minutes to obtain a preliminary mixture; (2) The preliminary mixed material is transferred to the feeding port of a twin-screw melt extruder, melt-extruded at 150°C, and granulated after cooling to obtain a modified masterbatch.
[0063] Specifically, the addition amount of the antiblocking agent filler is 0.6% of the mass of the FG600 base material film-grade polyester chips; the addition amount of the dispersant is 0.8% of the mass of the FG600 base material film-grade polyester chips.
[0064] The method for preparing the MLCC release film base film comprises the following steps: S1: According to the formula, layer A, layer B and layer C are dried in a drying tower at 170°C for 3 hours, and then vacuumed and sent to the surface layer 1 extruder, the core layer extruder and the surface layer 2 extruder for melt extrusion; S2: After passing through the three-layer co-extrusion die, the melt is cast onto a casting roll at 18°C to form a casting; the casting is preheated to 78°C by a longitudinal preheating roll, instantly heated to 100°C by an infrared lamp, and then stretched 2.8 times longitudinally. After stretching, it is quickly cooled by a cooling roll at 25°C to form a unidirectional sheet; the unidirectional sheet is preheated at 100°C, stretched 3.8 times transversely at 125°C, and fixed at 235°C for 10 seconds and then cooled at 50°C. After traction and winding, the MLCC release film base film is obtained.
[0065] Comparative Example 2 This comparative example is the same as Example 1, except that the material of layer A in Comparative Example 2 includes the following components in parts by weight: 60 pieces of special polyester chips; 30 parts of modified masterbatch.
[0066] Comparative Example 3 This comparative example is the same as Example 1, except that the material of layer A in Comparative Example 3 includes the following components in parts by weight: 98 pieces of special polyester chips; 30 parts of modified masterbatch.
[0067] Comparative Example 4 This comparative example is the same as Example 1, except that in the preparation process of the special polyester chips in Comparative Example 4, the mass ratio of terephthalic acid to 2,6-naphthalenedicarboxylic acid is 19:1, that is, 2,6-naphthalenedicarboxylic acid accounts for 5% of the mass of the mixture of the two.
[0068] Comparative Example 5 This comparative example is the same as Example 1, except that in the preparation process of the special polyester chips in Comparative Example 5, the mass ratio of terephthalic acid to 2,6-naphthalenedicarboxylic acid is 1.5:0, that is, no 2,6-naphthalenedicarboxylic acid is added.
[0069] Comparative Example 6 This comparative example is the same as Example 1, except that the material of layer A in Comparative Example 6 does not have a modified masterbatch.
[0070] Comparative Example 7 This comparative example is the same as Example 1, except that the material of layer A in Comparative Example 7 includes the following components in parts by weight: 70 pieces of special polyester chips; 3 parts of modified masterbatch.
[0071] Comparative Example 8 This comparative example is the same as Example 1, except that the material of layer A in Comparative Example 8 includes the following components in parts by weight: 70 pieces of special polyester chips; 35 parts of modified masterbatch.
[0072] Comparative Example 9 This comparative example is the same as Example 1, except that the modified masterbatch in Comparative Example 9 is prepared according to the following method: (1) Add 1820 parts of terephthalic acid, 30 parts of nano inorganic dispersion, 680 parts of ethylene glycol, 1 part of stabilizer, and 1 part of catalyst into the reactor, raise the temperature of the reactor to 235°C under nitrogen protection, and melt at constant temperature for 100 minutes; (2) After the material in step (1) is melted, the temperature in the reactor is raised to 290°C and the reaction is carried out at a constant temperature for 60 minutes; then the pressure in the reactor is reduced to 10 Pa, the temperature in the reactor is raised to 340°C, and the reaction is carried out at a constant temperature for 120 minutes. After the reaction is completed, small molecular impurities are removed by distillation during the reaction process, and finally the modified masterbatch is obtained by melt extrusion granulation.
[0073] The inorganic dispersion is prepared by following the steps below: 100 parts of the opening agent filler, 2 parts of the dispersant, and 700 parts of ethylene glycol were added into a high-speed mixer for dispersion and mixing at a dispersion speed of 1200 rpm for a dispersion time of 60 minutes to obtain an inorganic dispersion.
[0074] Comparative Example 10 This comparative example is the same as Example 1, except that the nucleating agent is Surlyn 8920 produced by DuPont.
[0075] Comparative Example 11 This comparative example is the same as Example 1, except that the opening agent filler is silicon dioxide with a particle size of 20-100 nm.
[0076] The various measured values shown in the various embodiments of the present invention and the comparative examples are measured according to the following methods.
[0077] Stiffness: After slitting, take a 2.5cm wide and 20cm long sample at each station, place the sample on a horizontal marble table at a temperature of 23±2℃ and a relative humidity of 50±5%, with the sample extending 10cm from the table. Use a ruler to measure the vertical height of the sample. The smaller the vertical height of the sample, the higher the stiffness of the sample. Measure the vertical height of all samples in turn, in units of 1mm, and take the average value as the stiffness value.
[0078] Warping height: After slitting, take a 100cm long film sample at each workstation and place it on a horizontal marble table at a temperature of 23±2℃ and a relative humidity of 50±5%. Observe the position where the warping is most serious and cut a 60cm*60cm warping sample. Place the sample with the warped surface facing up on the test platform and use a measuring ruler to measure the warping height of the four sides of the sample. This height is the highest height of the side, measured in 1mm. Measure the warping data of all samples in turn, and take the maximum value as the warping value.
[0079] Heat wrinkle: After slitting, take a 100cm long film sample at each workstation and place it on a horizontal marble table at a temperature of 23±2℃ and a relative humidity of 50±5% to observe whether there are wavy bumps on the film surface.
[0080] Thermal shrinkage: Use VMC322 two-dimensional shrinkage tester from Nantong Tai Precision Instrument Co., Ltd. to test according to the method specified in GB / T13542.2.
[0081] Roughness: The test was conducted using the SE800 surface roughness tester from Kosaka Research Institute of Japan according to the method specified in GB / T 1031-2009.
[0082] Friction coefficient: The test was conducted using the MXD-02 friction coefficient tester produced by Jinan Labthink Mechatronics Technology Co., Ltd. in accordance with the method specified in GB / T 10006-2021.
[0083] Mechanical properties: The elongation at break and elastic modulus were tested using a C610M intelligent electronic tensile testing machine produced by Jinan Languang Electromechanical Technology Co., Ltd. according to the method specified in ASTM D882-18.
[0084] The properties of the MLCC release film base film in the embodiments of the present invention and the comparative examples are shown in Table 1.
[0085] Among them, the difference between Comparative Example 1 and Example 1 is that the special polyester chips in Example 1 are replaced with FG600 base material film-grade polyester chips. Although the nucleating agent is also added, the stiffness and dimensional stability of the obtained MLCC release film base film are poor, warping and heat wrinkling occur on the film surface, and the elastic modulus is greatly reduced.
[0086] The difference between Comparative Example 2, Comparative Example 3 and Example 1 is that Comparative Example 2 reduces the amount of special polyester chips added, and the stiffness and dimensional stability of the MLCC release film base film obtained are poor, the film surface is warped, and the elastic modulus is reduced; Comparative Example 3 increases the amount of special polyester chips added, and the elongation at break of the MLCC release film base film obtained is significantly reduced, the film is easy to break, affecting the production film forming property and subsequent processing stability.
[0087] The difference between Comparative Example 4 and Example 1 is that in the preparation process of the special polyester chips in Comparative Example 4, the mass ratio of terephthalic acid and 2,6-naphthalene dicarboxylic acid is 19:1, that is, 2,6-naphthalene dicarboxylic acid accounts for 5% of the total mass of the two. The stiffness and dimensional stability of the prepared MLCC release film base film are poor, warping and heat wrinkling occur on the film surface, and the elastic modulus is greatly reduced.
[0088] The difference between Comparative Example 5 and Example 1 is that 2,6-naphthalene dicarboxylic acid is not added during the preparation of the special polyester chips in Comparative Example 5, and the stiffness and dimensional stability of the obtained MLCC release film base film are poor, warping and heat wrinkles occur on the film surface, and the elastic modulus is greatly reduced.
[0089] The difference between Comparative Example 6 and Example 1 is that the material of layer A in Comparative Example 6 does not have a modified masterbatch, and the friction coefficient of the obtained MLCC release film base film is too large, resulting in film adhesion during the production process and inability to produce normally.
[0090] The difference between Comparative Example 7, Comparative Example 8 and Example 1 is that Comparative Example 7 reduces the amount of modified masterbatch added, and the friction coefficient of the obtained MLCC release film base film is relatively large, which causes film adhesion during the production process and affects the production stability; Comparative Example 8 increases the amount of modified masterbatch added, and the roughness of the obtained MLCC release film base film becomes larger, which cannot meet the use requirements of the MLCC release film base film.
[0091] The difference between Comparative Example 9 and Example 1 is that the preparation method of the modified masterbatch is changed, and the roughness of the obtained MLCC release film base film becomes larger, which cannot meet the use requirements of the MLCC release film base film. At the same time, the friction coefficient becomes larger, affecting the production stability.
[0092] The difference between Comparative Example 10 and Example 1 is that the nucleating agent is Surlyn 8920 from DuPont, and the surface of the obtained MLCC release film base film is warped and heat-wrinkled, the stiffness and dimensional stability are reduced, and the mechanical properties are deteriorated.
[0093] The difference between Comparative Example 11 and Example 1 is that the opening agent filler is silicon dioxide with a particle size of 20-100 nm, and the friction coefficient of the obtained MLCC release film base film is too large, resulting in film adhesion during the production process and inability to produce normally.
[0094] It can be seen from the above data that the present invention adopts special polyester chips as the polyester film base material, and through the combination with the modified masterbatch, as well as the synergistic effect of the various components, the prepared MLCC release film base film has excellent stiffness, flatness and dimensional stability, and also has lower roughness, thus meeting the requirements of the release film base film for MLCC thin layer.
[0095] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A MLCC release film base film, characterized in that: The MLCC release film base film is an ABC three-layer co-extrusion structure, wherein layers A and C are surface layers, and layer B is a core layer; The materials of the A layer include the following components in parts by weight: Special polyester chips 70-95 parts; Modified masterbatch 5-30 parts; The materials of the B layer include the following components in parts by weight: Special polyester chips 90-98 pieces; 2-10 portions of high-speed material; The materials of the C layer include the following components in parts by weight: 50-80 pieces of special polyester chips; Special masterbatch 20-50 parts; The special polyester chips are prepared by esterifying and polycondensing a mixture of polyethylene terephthalate and polyethylene naphthalate with polyol, and then adding a nucleating agent and extruding and granulating.
2. The MLCC release film base film according to claim 1, characterized in that: The special polyester chips are prepared according to the following method: (1) Mix terephthalic acid and 2,6-naphthalene dicarboxylic acid in a container to obtain a mixture, then add ethylene glycol, a catalyst, and a stabilizer, and react at 90-120°C for 2-4 hours under the protection of an inert gas, then raise the temperature to 190-250°C, and continue to react for 4-6 hours to complete the esterification reaction; (2) The pressure is reduced to 10-60 Pa, and the temperature is increased to 240-265°C. The polycondensation reaction is continued for 5-12 hours. The obtained polycondensate is mixed with a nucleating agent, and granulated by melt extrusion to obtain special polyester chips.
3. The MLCC release film base film according to claim 2, characterized in that: The mass ratio of terephthalic acid to 2,6-naphthalene dicarboxylic acid is (1.5-9):
1.
4. The MLCC release film base film according to claim 2, characterized in that: The molar mass ratio of the mixture to ethylene glycol is 1:(1-1.1).
5. The MLCC release film base film according to claim 2, characterized in that: The amount of the catalyst added is (0.1-0.3)% of the total mass of the mixture; the amount of the stabilizer added is (0.02-0.2)% of the total mass of the mixture.
6. The MLCC release film base film according to claim 2, characterized in that: The nucleating agent is ethylene acrylic acid ionomer.
7. The MLCC release film base film according to claim 1, characterized in that: The modified masterbatch is prepared according to the following method: the antiblocking agent filler is blended with the special polyester chips and the dispersant, and the mixture is extruded and granulated by a twin-screw.
8. The MLCC release film base film according to claim 7, characterized in that: The particle size of the opening agent filler is 0.3-2.2 μm.
9. The MLCC release film base film according to claim 7, characterized in that: The addition amount of the opening agent filler is (0.6-3)% of the mass of the special polyester chips.
10. A method for preparing the MLCC release film base film according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: According to the formula, the A layer, the B layer and the C layer are sent to the extruder for melt extrusion; S2: After passing through the die, the melt is cast behind the chilled roller to form a thick sheet. After longitudinal stretching, transverse stretching, shaping, cooling, pulling and winding, the MLCC release film base film is obtained.
Citation Information
Patent Citations
Low oligomer modified polyester film capable of being easily extended and method for manufacturing same
CN113334886A
Low-roughness release film base film and preparation method thereof
CN113524848A
Thermoplastic resin composition
KR1020110070300A